Glutaminase isoforms expression switches microRNA levels and oxidative status in glioblastoma cells. - De los Santos-Jiménez, Juan; Campos-Sandoval, José Ángel; Márquez-Torres, Clara; Urbano-Polo, Nieves; Brøndegaard, David; Martín-Rufián, Mercedes; Lobo, Carolina; Peñalver Alonso, Ana; Gómez García, María del Carmen; Martín-Campos, Janet; Cardona Ramírez, Carolina; Castilla, Laura; et al. (BMC, 2021)
Glutaminase isoenzymes GLS and GLS2 play apparently opposing roles in cancer: GLS acts as an oncoprotein, while GLS2 (GAB isoform) has context specific tumour suppressive activity. Some microRNAs (miRNAs) have been implicated in progression of tumours, including gliomas. The aim was to investigate the effect of GLS and GAB expression on both miRNAs and oxidative status in glioblastoma cells. Microarray profiling of miRNA was performed in GLS-silenced LN229 and GAB-transfected T98G human glioblastoma cells and their wild-type counterparts. Results were validated by real-time quantitative RT-PCR. Oxidative status and antioxidant enzymes were determined by spectrophotometric or fluorescence assays in GLS-silenced LN229 and T98G, and GAB-transfected LN229 and T98G. MiRNA-146a-5p, miRNA-140-3p, miRNA-21-5p, miRNA-1260a, and miRNA-92a-3p were downregulated, and miRNA-1246 was upregulated when GLS was knocked down. MiRNA-140-3p, miRNA-1246, miRNA-1260a, miRNA-21-5p, and miRNA-146a-5p were upregulated when GAB was overexpressed. Oxidative status (lipid peroxidation, protein carbonylation, total antioxidant capacity, and glutathione levels), as well as antioxidant enzymes (catalase, superoxide dismutase, and glutathione reductase) of silenced GLS glioblastoma cells and overexpressed GAB glioblastoma cells significantly changed versus their respective control glioblastoma cells. Several miRNAs have been characterized as strong biomarkers of glioblastoma proliferation linked to both GLS silencing and GAB overexpression. Total glutathione is a reliable biomarker of glioblastoma oxidative status steadily associated to both GLS silencing and GAB overexpression. Glutaminase isoenzymes are related to the expression of some miRNAs and may contribute to either tumour progression or suppression through certain miRNA-mediated pathways, proving to be a key tool to switch cancer proliferation and redox status leading to a less malignant phenotype.
Keywords: Isoenzimas; Estrés oxidativo; Cáncer - Aspectos moleculares; Antioxidant enzymes; Cancer; Glioblastoma; Glutaminase; microRNA; Oxidative stress